KEPEMIMPINAN KEPALA SEKOLAH DALAM MENGELOLA SDN KEDUNGGALAR 4 DAN SDN BANGUNREJO KIDUL 4 KECAMATAN KEDUNGGALAR - Ruminten Ruminten; Widya Trio Pangestu; Djoko Hari Supriyanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2022)
This study aims to determine: 1) the principal's strategy in managing SDN Kedunggalar 4 and SDN Bangunrejo Kidul 4, Kedunggalar District, 2) the obstacles faced by the principal in managing SDN Kedunggalar 4 and SDN Bangunrejo Kidul 4 Kedunggalar District, 3) solutions to the obstacles faced the principal in managing SDN Kedunggalar 4 and SDN Bangunrejo Kidul 4, Kedunggalar District. This research method uses a qualitative approach with direct interview data collection techniques with related sources, namely school principals, teachers, and guardians of students at the two institutions. The results of the research on the principal's strategy in managing SDN Kedunggalar 4 and SDN Bangunrejo Kidul 4, First: 1) Planning preparation is carried out at the beginning of the new school year, 2) Management of learning programs is carried out by providing guidance to teachers, 3) Acceptance of students in collaboration with institutions PAUD and TK, 4) Procurement of facilities and infrastructure, 5) Division of school personal tasks according to ability, 6) Financial management is adjusted to technical guidelines (BOS), 7) Provide flexibility for the community to use school facilities, 8) Administrative management is carried out by school staff, 9) Information management by creating groups via whatsapp, 10) Maintaining good relations with school personnel, 11) School evaluation is carried out once a month, 12) Making a schedule for supervision. Second: the obstacles faced by the principal, namely 1) aspects of student acceptance, 2) aspects of time, 3) aspects of facilities and infrastructure, 4) financial aspects. Third: solutions to the obstacles faced by the principal, namely 1) aspects of student acceptance: Providing school supplies, 2) aspects of time: dividing attendance time and compiling a supervision schedule in two institutions, 3) aspects of facilities and infrastructure: procurement of facilities and infrastructure as well as trying to applying for aid funds, 4) financial aspects: making financial budget policies Keywords: Principal, Leadership, Management